Ecological Literacy in Islamic Education: Strengthening Environmental Awareness Through Tauhid-Based Learning - Taufikin, Taufikin; Yusdani, Yusdani (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Environmental education is key in promoting environmental literacy, but integrating religious principles in education for sustainability remains under-researched. This study examines the role of tauhid-based environmental literacy in Islamic education, focusing on its effectiveness in shaping students' environmental awareness. The study used a qualitative approach involving interviews, observations and document analysis in three Islamic primary schools known for their commitment to the environment. The results showed that integrating Islamic theological teachings with environmental literacy significantly increased students' awareness and responsibility towards the environment. The main mechanisms are theological teaching, experiential learning, and institutional support, strengthening sustainability practices together. However, challenges such as the lack of a structured curriculum, resources, and inconsistent institutional support hinder the full implementation of faith-based environmental education. Compared to secular models, tauhid-centered sustainability education offers a holistic approach that integrates ethical, spiritual and scientific aspects and promotes long-term behavioral change. This research contributes to the broader debate on faith-based environmental education by providing empirical evidence on the effectiveness of religion-integrated sustainability education. Future research should explore curriculum development and policy integration to institutionalize tauhid-based environmental literacy, ensuring its long-term impact in different educational contexts. Pendidikan lingkungan memiliki peran krusial dalam menumbuhkan kesadaran ekologi, namun integrasi prinsip berbasis agama dalam pembelajaran keberlanjutan masih kurang dieksplorasi. Studi ini menelaah peran literasi ekologi berbasis tauhid dalam pendidikan Islam, dengan fokus pada efektivitasnya dalam membentuk kesadaran lingkungan siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara, observasi, dan analisis dokumen di tiga sekolah dasar Islam yang diakui atas komitmennya terhadap lingkungan. Hasil penelitian menunjukkan bahwa integrasi ajaran teologi Islam dengan literasi ekologi secara signifikan meningkatkan kesadaran dan tanggung jawab lingkungan siswa. Mekanisme utama yang mendukung hal ini mencakup pengajaran teologis, pembelajaran berbasis pengalaman, dan dukungan institusional yang secara kolektif memperkuat praktik keberlanjutan. Namun, tantangan seperti kurangnya kurikulum yang terstruktur, keterbatasan sumber daya, dan dukungan institusional yang tidak konsisten masih menghambat implementasi penuh pendidikan ekologi berbasis agama. Dibandingkan dengan model sekuler, pendidikan keberlanjutan berbasis tauhid menawarkan pendekatan holistik yang menggabungkan dimensi etika, spiritual, dan ilmiah, serta mendorong perubahan perilaku jangka panjang. Studi ini berkontribusi pada diskursus lebih luas mengenai pendidikan lingkungan berbasis agama dengan memberikan bukti empiris tentang efektivitas pembelajaran keberlanjutan yang terintegrasi dengan nilai-nilai keagamaan. Penelitian selanjutnya perlu mengeksplorasi pengembangan kurikulum dan integrasi kebijakan untuk menginstitusionalisasikan literasi ekologi berbasis tauhid, guna memastikan dampak jangka panjang dalam berbagai konteks pendidikan.